2020
DOI: 10.1177/2158244020941844
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Online Counseling Among Undergraduates in Some Ghanaian Universities

Abstract: Counseling is an age-old practice with roots dating back to the 20th century. Twenty-first-century boom in technology has offered new opportunities for counseling practice, making it possible for counselors and clients to interact virtually without recourse to physical meetings. This study sought to investigate students’ experiences of online counseling in some Ghanaian universities. A qualitative phenomenological approach was used to examine the experiences of undergraduate students using online counseling. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Previous international studies have assessed and evaluated the potential of various digital MH care services and offer insights into the potential for such services in LMIC settings ( Arafat et al, 2021 ; Zhou et al, 2020 ; Hungerbuehler et al, 2016 ; Amos et al, 2020 ; Berry et al, 2019 ). However, limited research has been undertaken on digital MH care in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous international studies have assessed and evaluated the potential of various digital MH care services and offer insights into the potential for such services in LMIC settings ( Arafat et al, 2021 ; Zhou et al, 2020 ; Hungerbuehler et al, 2016 ; Amos et al, 2020 ; Berry et al, 2019 ). However, limited research has been undertaken on digital MH care in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…In coherence with our findings, globally, a range of digital platforms (social media, instant messaging applications, video conferencing, animations etc.) have been utilized as a viable method in raising mass awareness and providing care ( Siriwardhana et al, 2013 ; Hanisch et al, 2016 ; Trivedi et al, 2007 ; Arafat et al, 2021 ; Hungerbuehler et al, 2016 ; Maulik et al, 2017 ; Amos et al, 2020 ; Berry et al, 2019 ; Iqbal, 2020 ; Ifdil et al, 2020 ). Digital media-based MH content has been demonstrated as leading to increased healthcare-seeking behaviors among the population, another significant benefit of such services ( Siriwardhana et al, 2013 ; Hanisch et al, 2016 ; Trivedi et al, 2007 ; Arafat et al, 2021 ; Hungerbuehler et al, 2016 ; Maulik et al, 2017 ; Amos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These obstacles if addressed properly will make online counseling more successful and enjoyable. If not, students will stick to only face-to-face counseling and those who cannot, will resort to other means of solving their issues of which some may be detrimental (Amos, Bedu-Addo & Antwi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A study found out that accessibility, convenience, privacy, and mobility were some significant benefits they indicated concerning online counseling. On the contrary, loss of non-verbal cues, mistrust, and poor internet connectivity were their major obstacles to online counseling (Amos, Bedu-Addo, & Antwi, 2020). Despite the issues and challenges encountered by the students and teachers, appropriate interventions were provided in collaboration with the academic heads, class advisers and subject teachers.…”
Section: Discussionmentioning
confidence: 99%